THE TEACHER’S INFLUENCE IN CURRICULUM POLICY IMPLEMENTATION - NDLOVU, BY FRANCIS (IJRDO- Journal of Educational Research, 2017)
This paper looks at the role played by teachers in curriculum policy effectuation. Teachers / educators are the major pillars in the teaching and learning process. Without doubt the most important person in the practice curriculum is the teacher. With their knowledge, experience and competencies teachers are central to any curriculum policy improvement effort, they are responsible for introducing the curriculum in the classroom and outside education companies spend countless hours developing curriculum it is the teacher who knew best what the curriculum should look like. After, all they work directly with the students who are meant to benefit from the curriculum. The key to getting teachers committed to an innovation is to enhance their knowledge of the new policy or programme. Therefore policymakers should no longer assume that curriculum implementation is a process that directly translates into classroom reality. Teachers are the ones who ultimately decide the fate of any educational enterprise. Consequently, teachers’ attitudes, feelings and perceptions should not be devalued before the launching of any innovation.